Predictions of Accounting Grades. - Brown, Robert O. (The Accounting Review, 1966)
Abstract From the above comments it might be concluded that in 72 cases, grades in accounting could have been predicted within one grade plus or minus if disrupting personal factors had not been present. In only three cases did the accounting teacher feel that the high school grade overrated the students' abilities. In all fairness it should be pointed out that in the cases of the three students who had high school averages of C but who made unexplained E's in accounting, the aptitude and entrance tests gave both students an E on each test. The third student received a C and a D respectively on the two tests. Based on this study, it appears that high school grades are superior to the scores from the aptitude test and the college entrance test for advising, evaluating a group, and predicting grades for accounting students. The old argument appears to be overworked - "there is a great difference in grading practices between small and large high schools." Three misses in seventy-five cases might seem excessive when decisions affecting careers are being made. However, in all three cases in which the college record was not as good as the high school record, the more serious error of underrating the student would not have been made. Capable students such as the "late comers" would not have been overlooked. It should be noted that no high school D student earned either an A or B in accounting. Four students with low aptitude test scores and seven with low college entrance scores earned B's or A's. The odds of passing over an outstanding student because of a low test score are too high when the aptitude or college entrance tests are used as evaluators.